2022
DOI: 10.1007/s00204-022-03284-4
|View full text |Cite
|
Sign up to set email alerts
|

Medaka embryos as a model for metabolism of anabolic steroids

Abstract: In anti-doping science, the knowledge of drug metabolism is a prerequisite to identify analytical targets for the detection of misused prohibited substances. As the most obvious way to study xenobiotic metabolism, the administration to human volunteers, faces ethical concerns, there is a need for model systems. In the present study, we investigated whether Oryzias latipes (medaka) embryos might be an alternative, non-animal test model to study human-like metabolism. In the present study, we exposed medaka embr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…This study also demonstrated the importance of mass spectrometry. MS is the current technology of choice for detecting and quantifying proteins and metabolites, as it is adaptable to virtually any type of sample, ranging from cells and neurons to subcellular organelles, tissues, and even whole embryos [ 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. Mass spectrometers can directly detect intact proteins, peptides, post-translational modifications, and metabolites with high specificity, usually sub-mDa (sub-ppm) mass accuracy, and the capability for both discovery (untargeted) and targeted studies.…”
Section: Discussionmentioning
confidence: 99%
“…This study also demonstrated the importance of mass spectrometry. MS is the current technology of choice for detecting and quantifying proteins and metabolites, as it is adaptable to virtually any type of sample, ranging from cells and neurons to subcellular organelles, tissues, and even whole embryos [ 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. Mass spectrometers can directly detect intact proteins, peptides, post-translational modifications, and metabolites with high specificity, usually sub-mDa (sub-ppm) mass accuracy, and the capability for both discovery (untargeted) and targeted studies.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the steroidogenic enzymes P450 aromatase, 11β-hydroxylase and 3β-hydroxysteroid-dehydrogenase has been detected prior to hatch (21). Indeed, pre-hatch medaka have been proposed as a model for studying the metabolism of anabolic steroids and have been demonstrated to produce a number of metabolites when exposed to metandienone including three mono-hydroxylated and one reduced metabolite that are produced by humans (22). 13.…”
Section: Initial Considerations and Limitationsmentioning
confidence: 99%
“…With the existing and further growing number of non‐approved substances with potential for misuse in sports, for which little data on metabolism (especially in humans) exist, adequate models mimicking human metabolic biotransformations are extremely valuable. Therefore, Liu et al assessed medaka embryos as model “organisms” for the metabolism of AASs as exemplified by means of metandienone 48 . The Oryzias latipes embryos were exposed to metandienone up to 8 days at 50 μM concentrations, and metabolites formed were enzymatically hydrolyzed using β‐glucuronidase and purified and concentrated by liquid–liquid extraction (LLE) before analysis.…”
Section: Anabolic Agentsmentioning
confidence: 99%
“…34 for the metabolism of AASs as exemplified by means of metandienone. 48 The Oryzias latipes embryos were exposed to metandienone up to 8 days at 50 μM concentrations, and metabolites formed were enzymatically hydrolyzed using β-glucuronidase and purified and concentrated by liquid-liquid extraction (LLE) before analysis. Three monohydroxylated as well as one C C double bond-reduced metabolites were observed using both GC-high-resolution/ high-accuracy mass spectrometry (HRMS) and LC-HRMS, with the former approach further requiring trimethylsilylation.…”
Section: Initial Testing Procedures (Itps)-comprehensive Screening An...mentioning
confidence: 99%